Consumption of red-hot chili pepper increases symptoms in patients with acute anal fissures. A prospective, randomized, placebo-controlled, double blind, crossover trial Efeito da pimenta vermelha nos sintomas de pacientes com fissuras anais agudas - Pravin J. Gupta (Arquivos de Gastroenterologia, 2008)
BACKGROUND: Red-hot chili pepper and other spices have been blamed for causing or exacerbating symptoms of anal pathologies like anal fissure and hemorrhoids. AIM: To determine if consumption of chilies increases symptoms of acute anal fissures. METHODS: Individual patients were randomized to receive capsules containing chili or placebo for one week in addition to analgesics and fiber supplement. Patients were asked to note score for symptoms like pain, anal burning, and pruritus during the study period. After 1 week, cross over treatment was administered to the same group of patients with the same methodology and results were noted at the end of 2 weeks. RESULTS: Fifty subjects were recruited for this study. Forty three of them completed the trial (22 in the chili group and 21 in the placebo group). The daily mean pain score was significantly lower in the placebo group in the study period. Score 2.05 in chili group and 0.97 in placebo group. There was a significant burning sensation experienced by the patients in the chili group (score 1.85 for the chili group vs 0.71 for the placebo group). Patient’s mean recorded improvement score was significantly higher after taking placebo. Eighty one point three percent patients preferred placebo while 13.9% preferred chilies. Two patients had no preference. CONCLUSION: Consumption of chili does increase the symptoms of acute anal fissure and reduces patient compliance. RACIONAL: A pimenta vermelha e outras especiarias têm sido responsabilizadas por agravar a sintomatologia das doenças anais, tais como fissuras e hemorróidas. OBJETIVO: Determinar se o consumo de pimentas vermelhas aumentaria os sintomas em fissuras anais agudas. MÉTODOS: Pacientes foram recrutados e randomizados para receber cápsulas contendo pimenta ou placebos por 1 semana, somadas a analgésicos e suplementos de fibras. Foi solicitado que anotassem um escore de sintomas, tais como dor, queimação anal, prurido durante o período de estudo. Após 1 semana o tratamento foi cruzado e administrado ao mesmo grupo de pacientes com a mesma metodologia e os resultados foram anotados ao final de duas semanas. RESULTADOS: Cinqüenta pacientes foram selecionados e 43 completaram o estudo (22 no grupo pimenta e 23 no grupo placebo). O escore médio diário de dor foi significativamente mais baixo (2,05 no grupo pimenta e 0,97 no grupo placebo). A sensação de queimação foi sentida de modo significativo no grupo pimenta (1,85 para o grupo pimenta vs 0,71 para o grupo placebo). O escore de melhora dos sintomas foi significantemente alto após tomar o placebo. Oitenta e um virgula três porcento dos pacientes preferiram tomar placebo contra 13,9% que preferiram pimenta. Dois pacientes não referiram preferências. CONCLUSÃO: O consumo de pimentas agrava os sintomas de fissuras anais agudas.